Influences of Dynamic Debris Jams on a Bridge Pier - Zhang, Wenjun (Université d'Ottawa / University of Ottawa, 2023)
Sediment material around the base of a bridge pier is moved by the flow velocity and associated turbulence. This phenomenon is generally termed as local scour and can lead to undermining the structure and increase its possibility of failure. Numerous factors can affect bridge pier scour and they have been investigated for decades. Debris jams, one of these factors, could significantly contribute to bridge failure as some field examples and experimental investigations pointed out. Woody debris accumulation on the front of either single or multiple bridge piers can result in deeper pier scour and extra load exerted on the pier. Several studies have already investigated the influence of woody debris on pier scour in terms of static woody debris. In addition, HEC-18 (2012) also proposed a design code to estimate scour depth in the presence of woody debris jam. However, in these studies, the woody debris jam was considered to be static, whereas a woody debris jam accumulates piece by piece, growing to a debris jam with a shape most akin to a half-cone, and then may even eventually break up and be carried in pieces downstream. Therefore, this research investigated the evolution of the loading onto and scouring around a bridge pier in the presence of dynamic debris jams. In this study, the temporal evolution of the bridge pier scours was monitored during the development of dynamic debris jams. Experimental modeling was conducted to explore the influence of dynamic debris jam on bridge pier scour using a scale of 30 by employing both dowels and seedling trees. It was found that the dynamic debris jam of dowels could last 10-20 minutes and reach a critical size, then fail and subsequently reform. In addition, the first debris jam had an obvious influence on scour depth which correlated to the blockage generated by the debris jam; however, the influence of the subsequent debris jam depended on its size compared to the previously formed one. For the dynamic debris jam using seedling trees, the debris jam lasted for a longer time once it formed, and it could lead to twice the maximum scour depth compared to that generated in the absence of the debris jam, which is the same with dowels debris jam. In addition, the hydraulic head induced by the debris jam was correlated to the blockage of the debris jam and the flow Froude number irrespective of whether the dynamic debris jam was made of dowels or seedling trees. Additionally, blank control tests in the absence of a debris jam were used along with previous data gleaned from the literature to develop and test new multigene genetic programming (MGGP) models for the temporal evolution of scour. The MGGP model, using the non-dimensional variables from the empirical equations, can reach a better accuracy than the empirical equations, which indicates the ability of the model to optimize the empirical equations. The temporal evolution of load exerted onto the bridge pier with a dynamic debris jam was also measured. Experimental tests were performed to investigate the additional debris jam drag force exerted onto the bridge pier using both dowels and seedling trees in the presence of a fixed flume bed. Likewise, the dynamic debris jam of dowels lasted for about 10-20 mins, while those formed by the seedling trees, once formed, could last over 50 mins. The investigation demonstrated that the drag coefficient of the seedling trees jam was higher than that of the dowels jam. More importantly, a spike in the drag force was also observed irrespective of whether the jams were formed by dowels or seedling trees. Detailed investigation of the flow field around the debris jam and pier provided insight into the mechanics of debris jams. Three half-cone-shaped debris jams of the same dimensions were designed and built. The three jams were fabricated using: a) 20 cm long dowels, b) 30 cm long dowels, or c) a 3D printer. For each jam, four sections were measured using an Acoustic Doppler Velocimeter (ADV). The results indicated that the flow fields around the 20 cm length dowel jam and the 30 cm length dowel jam were similar. In addition, the section behind the pier and debris jam showed divided zones termed herein as the accelerated high-velocity zone, the high shear transition zone, and the wake dead zone. As for the drag coefficient, the 20 cm length dowels jam and 30 cm length dowels jam shared a very close magnitude of 1.7, but the drag coefficient of the 3D printer debris jam was only 0.88 which indicated the debris jam built by individual pieces behaved differently than the block jam.
Keywords: Dynamic Debris jam; Bridge pier scour; Flow field; Debris loads